2019
DOI: 10.1109/access.2019.2895998
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Time Scales Analysis for Identifying Congestive Heart Failure Based on Heart Rate Variability

Abstract: It is well known that electrocardiogram heartbeats are substantial for cardiac disease diagnosis. In this paper, the best time scale was investigated to recognize congestive heart failure (CHF) based on heart rate variability (HRV) measures. The classifications were performed on seven different time scales with a support vector machine classifier. Nine HRV measures, including three time-domain measures, three frequency-domain measures, and three nonlinear-domain measures, were taken as feature vectors for clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…In most cases, RR intervals of less than 0.4 s may indicate that an R peak was incorrectly detected within a normal RR interval, while > 2.0 s may indicate that an R peak was missed between two normal RR intervals [10]. Therefore, RR intervals less than 0.4 s or greater than 2.0 s were deleted from the original data.…”
Section: Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, RR intervals of less than 0.4 s may indicate that an R peak was incorrectly detected within a normal RR interval, while > 2.0 s may indicate that an R peak was missed between two normal RR intervals [10]. Therefore, RR intervals less than 0.4 s or greater than 2.0 s were deleted from the original data.…”
Section: Datasetmentioning
confidence: 99%
“…In this study, nine traditional features including the time, frequency, and nonlinear domains were first calculated [10]. Time domain features include MEAN, SDNN, and RMSSD [13], where the MEAN is the average value of the RR interval, the SDNN was used to evaluate the overall variability of the heart rates, and the RMSSD was used to evaluate the short-term variability of the heart rates.…”
Section: Hrv Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, most of the literature on using machine learning for heart disease diagnosis utilized two major techniques: the ANN [16,17,18,19] and the SVM [20,21,22,23]. They both have high classification accuracy, but they suffer from low learning speed when the number of instances or the number of features is huge.…”
Section: Dis-cat3mentioning
confidence: 99%
“…In [ 20 ], a parametric estimation of SampEn on real RR series from both NSR and CHF subjects was proven to be feasible. SampEn has also been widely chosen as a representative feature in novel CHF detection algorithms based on HRV measures and classifiers such as support vector machine (SVM) [ 21 , 22 , 23 , 24 ], which provide effective and computationally efficient tools to automatically diagnose CHF patients. Though diagnosing heart failure with long-term ECG signals (usually 24 h) may lead to accurate results [ 25 , 26 ], some studies have shown that short-term (usually 5 min) ECG recordings could also provide valuable information [ 27 , 28 ], thus the focus of research has recently switched to low-cost, non-invasive, and lightweight classification methods that are based on short-term HRV analysis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%